The Loving Spirit - Du Maurier, Daphne (London Heinemann, 1958)
A saga of four generations of shipbuilders and merchant mariners in a village on the Cornish coast.
Keywords: England--Cornwall (County) -- England -- Man-woman relationships -- Manners and customs